TIME MANAGEMENT MODEL IN THE ENTERPRISE PERSONNEL SECURITY SYSTEM - Сергій Шевченко; Марта Оліховська; Роксолана Винничук; Марія Бардадим; Ростислав Дарміць; Ольга Чепець (Фінансово-кредитна діяльність: проблеми теорії та практики, 2025)
The purpose of the study is to increase the level of personnel security of an enterprise by integrating time management models adapted to the conditions of modern challenges and martial law. The work used the methodology of system analysis, which allowed for a comprehensive consideration of the problem and the formation of a multi-level model of working time management. The results of the study identified key external and internal factors (political, economic, social, technological) that affect personnel security in crisis conditions. It is proven that effective time management allows reducing the level of stress of personnel and the risk of losing key employees, thereby strengthening the personnel security of the enterprise; the relationship between the implementation of a hierarchical system of priorities in the distribution of tasks and increasing the enterprise's resilience to external shocks (in particular, military ones) is established; the features of the application of time management models in martial law conditions are characterized (flexibility of schedules, reserving time for critical functions, ensuring communication and support for employees). It is determined that the proposed model allows for timely assessment of the effectiveness of the current time management system and to identify changes during the initial period of time.